Development and Implementation of a Bilingual Counseling Certificate Program - Claudia Interiano-Shiverdecker; Derek Robertson; Elias Zambrano; Ashley Morgan; Jacqueline Cantu Contreras (Teaching and Supervision in Counseling, 2021)
The ever-growing population of Spanish-speakers in the United States increases the need for counselors to provide services in languages other than English. Yet, very few counselor education programs offer training specifically aimed at providing bilingual counseling services. The authors introduce important elements of bilingual counseling training and describe the implementation of these features into a certificate designed to train competent, bilingual clinical mental health and school counselors. Implications for counseling pedagogy, practice, supervision, and research are discussed.
Keywords: bilingual counseling; certificate; Spanish-speaking